(untitled) (Plant Tissue Culture and Biotechnology, 2022)
An efficient, and reproducible in vitro regeneration protocol was developed for three varieties of chickpea (Cicer arietinum L.) named Barichhola-9, Barichhola-10, and Barichhola-11 using embryos with decapitated root tips as explants. The best response towards callus induction was obtained on MS medium supplemented with a combination of 2.0 mg/l BAP and 0.3 mg/l NAA. MS medium containing 3.0 mg/l BAP alone provided the highest number of shoots from the induced callus. MS medium with 0.5 mg/l NAA was found to be the best for root induction from in vitro regenerated shoots in all three varieties of chickpea. In vitro regenerated well-rooted plantlets were transplanted into a small pot containing a mixture of soil and cocodust for acclimatization. Regeneration responses were found to be identical for the three varieties of chickpea used in this study. The results of the present investigation will facilitate the in vitro regeneration of chicpea varieties as well as further genetic improvement of this economically valuable crop species through genetic transformation. Plant Tissue Cult. & Biotech. 32(2): 205-216, 2022 (December)